ARE WE THERE YET? GENDER QUOTAS IN UNIVERSITY HIERARCHIES: THE CASE OF COLOMBIA (2022)
The year 2022 was set as the deadline in the Colombian National Development Plan for reaching gender parity in all public directives. As we approach the time limit, this study takes the lead on examining the impact of the national gender quota by comparing official reports and empirical data. Official records show ongoing growth in the rate of female representation among the top decision-making levels at reporting organizations, yet closer analyses of quota-regulated universities’ performance identify divergent results. Moreover, records of job positions filled by women are systematically omitted, despite being required by law, which raises further questions about the quota’s potential to foster gender equality at the organizational level. This research addresses this data gap by examining whether having a larger proportion of women among various organizational bodies influences their rate of election to decision-making roles and explores current corporate equality strategies to provide a more comprehensive analysis of the quota’s impact. © 2022, Corvinus University of Budapest. All rights reserved.